Determinants of credit to households in a life-cycle model - Michał Rubaszek; Dobromil Serwa (European Central Bank (ECB), 2012)
This paper applies a life-cycle model with individual income uncertainty to investigate the determinants of credit to households. We show that the value of household credit to GDP ratio depends on (i) the lending-deposit interest rate spread, (ii) individual income uncertainty, (iii) individual productivity persistence, and (iv) the generosity of the pension system. Subsequently, we provide empirical evidence for the predictions of the theoretical model on the basis of data for OECD and EU countries.
Keywords: E21; E43; E51; 330; banking sector; Household credit; life cycle economies